Antiquity of cleptoparasitism among bees revealed by morphometric and phylogenetic analysis of a Paleocene fossil nomadine (Hymenoptera: Apidae). (July 2017) - DEHON, MANUEL; PERRARD, ADRIEN; ENGEL, MICHAEL S.; NEL, ANDRÉ; MICHEZ, DENIS
Abstract: Cleptoparasitism is a way of life involving the theft of resources by one animal from another. This behaviour occurs in many bee tribes but its origin and evolution remain obscure, particularly owing to the relative scarcity of bees in the fossil record. Hitherto, no fossil evidence has been recorded to trace the origin of cleptoparasitim among bees. In the current study, we present the first cleptoparasitic bee fossil, providing analyses of its taxonomic affinities and a complete description. The specimen also happens to be one of the earliest bee fossils, having been discovered in the spongo‐diatomitic volcanic paleolake of Menat (Paleocene) in France. We employed geometric morphometrics of the forewing shape to assess the taxonomic affinities of the fossil with modern apoid tribes. Our dataset included 979 specimens representing 50 tribes and 225 extant species. Based on linear and geometric morphometrics, we demonstrate that the fossil's forewing shape is similar to that of Apidae, and particularly to that of the tribe Epeolini (Nomadinae). The fossil is described as Paleoepeolus micheneri gen.n., sp.n. and provides the first direct evidence on the antiquity of cleptoparasitism among bees. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:BBBE22176CAE48F9851F716B813DFEBF .